2008
DOI: 10.2109/jcersj2.116.921
|View full text |Cite
|
Sign up to set email alerts
|

Development of ceramic microcoils with 3D-herical/spiral structures

Abstract: Various modified CVD processes, such as modified hot filament method, vapor phase diffusion process, in-situ CVD process, catalytic CVD process, for the preparation of ceramics single crystals and fibers were developed. The preparation conditions, morphologies, microstructure and properties of transition metal carbides, nitrides, borides, silicides, sulfides, etc were examined. We have first found that various ceramic fibers with 3D-helical/spiral structure, such as Si3N4, carbon, TiC, TiO2, etc. were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
8
0
2
Order By: Relevance
“…Studies performed by Chen et al 63 showed that as-synthesised carbon coils could be elongated by ~ 42% (Figure 19). Further studies by Motojima 50 revealed that helical fibres with circular cross section could be expanded to between 4.5 times and 15 times that of the original coil length. By contrast, a coil with flat cross section could only be extended to 1.5 times its original coil length.…”
Section: Properties and Uses Of Chsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies performed by Chen et al 63 showed that as-synthesised carbon coils could be elongated by ~ 42% (Figure 19). Further studies by Motojima 50 revealed that helical fibres with circular cross section could be expanded to between 4.5 times and 15 times that of the original coil length. By contrast, a coil with flat cross section could only be extended to 1.5 times its original coil length.…”
Section: Properties and Uses Of Chsmentioning
confidence: 99%
“…However, helical material several microns in diameter has been synthesised, indicating that metal particle size was not the only factor that determined carbon morphology. 50,51 The catalyst particle shape has also been proposed to control the carbon growth. Motojima 50 showed that different crystal faces of a metal particle could show variable coil growth.…”
Section: Growth Mechanisms Of Chsmentioning
confidence: 99%
See 2 more Smart Citations
“…[212][213][214] ZrS 2 bildet Rollen. [215,216] Natürlicher Rutil (TiO 2 ), Cosalit (Pb 2 Bi 2 S 5 ), Stibnit (Sb 2 S 3 ) und Chalcotrichit (Cu 2 O) bilden verwundene faserfçrmige Kristalle, [217] ebenso wie Magnesium-reicher Calcit. [218] Quarz [219][220][221][222][223][224][225] (Abbildung 9 a) gesellt sich als verwundener Makrokristall (100 mm < h < 3 cm) zum Phosgenit von Sowerby [57] und dem Stibnit von Wada (Abbildung 5).…”
Section: Geschichteunclassified